2012
DOI: 10.1017/s2044251311000129
|View full text |Cite
|
Sign up to set email alerts
|

Non-Precluded Measures in Indian International Investment Agreements and India's Regulatory Power as a Host Nation

Abstract: This article provides the first-ever detailed analysis of Non-Precluded Measures (NPM) provisions in India's International Investment Agreements (IIAs) from the perspective of India's regulatory power as a host nation. It critically analyses NPM provisions in fiftyseven Indian IIAs by studying the divergence in their formulation and argues that the present formulation of NPM provisions in Indian IIAs is inadequate for the exercise of regulatory power by India for all its policy needs. Hence, in the light of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Relying on the ICJ's holding in the Oil Platforms case, 43 Regarding Article 25, the committee, identified it as a secondary rule 45 and ruled that, -the excuse based on customary international law could only be subsidiary to the exclusion based on Article XI.‖ 46 In other words, the CMS annulment committee suggested that the tribunal may first consider whether an act cannot be considered a potential treaty breaches by a treaty NPM provision (Article XI) that is applied as lex specialis, and then it should consider Argentina precluded from liability for a breach under customary international law (Article 25) applied as lex specialis. In its analysis, the committee differentiated the two defenses and pointed out that Article XI -covers measures necessary for the maintenance of public order or the protection of each Party's own essential interests, without qualifying such measures.....while Article 25 subordinates the state of necessity to four conditions‖ 47…”
Section: A the Relationship Between Non-precluded Measures And State Of Necessitymentioning
confidence: 99%
See 1 more Smart Citation
“…Relying on the ICJ's holding in the Oil Platforms case, 43 Regarding Article 25, the committee, identified it as a secondary rule 45 and ruled that, -the excuse based on customary international law could only be subsidiary to the exclusion based on Article XI.‖ 46 In other words, the CMS annulment committee suggested that the tribunal may first consider whether an act cannot be considered a potential treaty breaches by a treaty NPM provision (Article XI) that is applied as lex specialis, and then it should consider Argentina precluded from liability for a breach under customary international law (Article 25) applied as lex specialis. In its analysis, the committee differentiated the two defenses and pointed out that Article XI -covers measures necessary for the maintenance of public order or the protection of each Party's own essential interests, without qualifying such measures.....while Article 25 subordinates the state of necessity to four conditions‖ 47…”
Section: A the Relationship Between Non-precluded Measures And State Of Necessitymentioning
confidence: 99%
“…They contain formulations such as 45 See ILC, Report of the Study Group of the International Law Commission, Fragmentation of 46 CMS Annulment, supra (note 37), para 132. 47 Ibid, para 130. 48 -require‖, 50 -directed to‖ 51 and -have to be taken for reasons of.‖ 52 These languages of the nexus requirement functions as vital link between the taken measures and the permissible objectives in the NPM clause.…”
Section: B the Structure Of Non-precluded Clausesmentioning
confidence: 99%
“…So, it essentially refers to certain circumstances, and not to an objective like an 'essential security interest'. 75 However, here we discuss CEE as a permissible objective because it can include different regulatory objectives within its domain.…”
Section: Circumstances Of Extreme Emergencymentioning
confidence: 99%
“…Trade agreements enhance competition from foreign enterprises and require compliance with international norms and laws. Entrepreneurs must strategically evaluate trade agreements to maximize market access and minimize risk (Ranjan, 2012).…”
Section: Analyzing Trade Policies: Implications For Entrepreneurshipmentioning
confidence: 99%